CURRENT STATUS OF NANO CHARACTERIZATION PRODUCT PT. JJ EXECUTIVE INTERNATIONAL - Jefry Jefry (Jurnal Sains Materi Indonesia, 2007)
CURRENT STATUS OF NANO CHARACTERIZATION PRODUCT PT. JJ EXECUTIVE INTERNATIONAL. Material analysis Instrumentation and characterization equipment are rapidly develop in this recent decade. Many new techniques and new instrumentation are introduced for researcher to overcome the limitation and conventional technique as in last decade